2020
DOI: 10.31616/asj.2020.0224
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Coronavirus Disease 2019 in Spine Surgery: A Rapid National Consensus Using the Delphi Method via Teleconference

Abstract: The magnitude and potential duration of the current coronavirus disease 2019 pandemic is something that most doctors currently in practice have yet to experience. While considerable information regarding COVID-19 is being published every day, it is challenging to filter out the most relevant or appropriate information for our individual practice. The Spine Society of Singapore convened via a teleconference on April 24, 2020 to collaborate on a national level and share collective wisdom in order to tackle the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The lack or unavailability of clear guidelines on appropriate remote health care for different patients was a major challenge [ 52 , 66 ]. For instance, no international guidelines or best practices exist for the management of patients with cancer in any emergency situation during the pandemic [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack or unavailability of clear guidelines on appropriate remote health care for different patients was a major challenge [ 52 , 66 ]. For instance, no international guidelines or best practices exist for the management of patients with cancer in any emergency situation during the pandemic [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the appropriate selection of patients requires a comparison between virtual treatments and in-person visits. Authors in [ 52 ] conducted a teleconference with 13 spine surgeons from across various hospitals to serve as a panel of experts. They discussed topics related to surgeon repurposing, spine telehealth introduction, service continuity, preoperative testing, spinal surgery triaging, new challenges in spine surgeries and post-pandemic preparations.…”
Section: Taxonomymentioning
confidence: 99%
“…In addition, the majority of national and international orthopaedic conferences, training programs, and workshops have been postponed or cancelled. Therefore, there is a strong need to make a new delivery system for education to our colleagues, residents, and fellows [7,8,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or human coronavirus 2019 (HCoV- 19), was first detected in Wuhan, China, in November 2019 [1]. Its potential to generate explosive outbreaks in confined settings and cross borders following human mobility patterns has already been reported IRB status: This nationwide survey study was approved by the Institutional Review Board of the Uijeongbu St. Mary's Hospital (IRB number: UC20QADI0086), College of Medicine, The Catholic University of Korea, and an informed written consent was waived from the participants for the survey study and publication of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current triage systems should be more aware of their hazardous and infective features. (24)(25)(26)…”
Section: Special High-risk Groups In Triagementioning
confidence: 99%